Perjumpaan Psikologi dan Tasawuf Menuju Integrasi Dinamis - Mujiburrahman, Mujiburrahman (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2017)
The problematic relations between religion and science do not only occur in Western societies but also in Muslim societies. While early modern Muslim reformists strongly encouraged Muslims to adopt modern sciences, later reformists argued that modern sciences should be Islamized. The idea of Islamization of knowledge has been widely discussed and contested. Another alternative to the idea of Islamization is integration. The integration should be dynamic in the sense that they interact in a mutually illuminating, enriching and renewing mode. This paper presents the possibility of the dynamic integration between Psychology and Sufism. Some modern psychologists argue that Sufism is not scientific because it is not based on empirical observation, while some others say that modern psychology?s denial of metaphysical realities is in fact not based on strong evidence but assumptions. In the light of integration, instead of opposing the two disciplines to one another, one actually can draw the lines where modern psychology and Sufism meet and separate. The rational and empirical basis of modern psychology can be enriched, renewed and illuminated by the metaphysical and spiritual basis of Sufism, and vise-versa.